Perception of bumiputra and non-bumiputra students on becoming professional accountants - Noor Asidah binti Abd. Rashid (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
This study examines the undergraduate accounting students' perceptions on becoming professional accountants in the Malaysian context. Using questionnaire survey, this study examines the Bumiputra and non-Bumiputra students' intention to pursue the professional qualification, as well as to determine what are the motivational factors for Bumiputra and non-Bumiputra accounting students in Malaysia to pursue professional qualification. This study investigates whether there is a significant difference between the perception of Bumiputra and non-Bumiputra students on pursuing the professional qualification. In addition, this study also determines whether there is an association between perception and intention to pursue the professional qualifications for Bumiputra and non-Bumiputra students. This study uses questionnaires to collect the data. The sample group consists of final year accounting students who are currently studying in five public universities and three private universities. Means and regressions were used to conduct the tests in the study. The main statistical technique used to test the hypotheses is regression. The results indicate that the majority of Bumiputra and non-Bumiputra students do intend on becoming professional accountants. “Work experience in the field of accounting” is the primary motivational factor for both groups in pursuing professional qualification. Further results show that there are only a few significant differences of perceived benefits and negative aspects on becoming professional accountants between Bumiputra and non-Bumiputra students. Negative perception is strongly negatively associated with intention to pursue professional qualification. Interestingly, the Bumiputra students seem to have more intention to pursue their professional qualification than non-Bumiputras. The results provide useful insights to relevant institutions such as the Ministry of Education and the professional bodies in alleviating the negative perceptions on pursuing the professional qualification in order to increase the number of professional accountants as targeted to 65,000 in the year 2020.